Characteristics of non-methane hydrocarbons and methane emissions in exhaust gases under natural-gas/diesel dual-fuel combustion. (15th April 2021) - Lee, Seokhwan; Kim, Changgi; Lee, Sunyoup; Oh, Sechul; Kim, Junghwan; Lee, Jeongwoo
Highlights: Effects of fuel fractions and diesel SOI on THC are discussed. Methane is related with crevice effect and bulk quenching. NMHC is related with wall-wetting of diesel spray. MFB50 position has strong influence on heat transfer loss. RCCI improved the BTE with reduction of THC emissions. Abstract: In dual-fuel combustion, the levels of total hydrocarbon (THC) emissions have increased, unlike the neat diesel compression ignition (CI) combustion. Intuitively, it can be inferred that most THC emissions are produced by the crevice effect of low-reactivity fuels (high-volatility fuels) under dual-fuel combustion. Additionally, it is possible that high levels of THC emissions are produced by dual-fuel combustion. If reactivity-controlled compression ignition (RCCI) combustion is applied by advancing the diesel injection timing to improve the premixing conditions, the occurrence of the wall-wetting effect may induce the production of high levels of THC emissions owing to incomplete combustion. Thus, in this study, the characteristics of non-methane hydrocarbons (NMHC) and methane emissions under general dual-fuel combustion conditions (diesel injection timings before top dead center (BTDC) 0 and 30 crank angle degree (CAD)) and RCCI conditions (diesel injection timings at 60 and 84 CAD BTDC) were investigated under a low-load in a 6-L heavy-duty engine. The natural gas fraction varied from 50% to the maximum level considering the combustion stability (coefficient of variance of indicated mean effective pressure). The results revealed that the overall THC emissions from the general dual-fuel combustion were higher compared with those of RCCI combustion, owing to the methane emissions from the squish area and the lower average in-cylinder temperature. Notably, methane emissions were dominant in the THC emissions (52–87%) under the general dual-fuel combustion condition, while NMHC emissions were a major part of the in THC emissions (61–87%) under the RCCI regimes. Hence, combustion inefficiency is a major concern in dual-fuel combustion. In this study, this problem was resolved by advancing the diesel injection timings. The findings in this study can be useful in the design of oxidation catalysts, regardless of whether the combustion regime is a general dual-fuel combustion or RCCI combustion considering the portion of methane emissions in the exhaust gas. Additionally, it is known that the RCCI combustion is superior to the general dual-fuel combustion with respect to higher thermal efficiency and low harmful THC emissions.